Algal oil gives control of long‐chain omega‐3 levels in full‐cycle production of Atlantic salmon, without detriment to zootechnical performance and sensory characteristics - Ester Santigosa; Rolf Erik Olsen; Angelico Madaro; Viviane Verlhac Trichet; Ian Carr (Journal of the World Aquaculture Society, 2023)
Abstract The levels of eicosapentaenoic (EPA) and docosahexaenoic (DHA) in salmon fillets have decreased because of the progressive replacement of fish oil (FO). This study contributes to enabling the sustainable growth of aquaculture by confirming the effects of partially or fully replacing FO with microalgal oil (AO) on growth, muscle fatty acid profiles, and muscle quality of farmed Atlantic salmon. Crucially, this is now done throughout the entire post‐smolt production cycle and up to a harvest weight of 3 kg. Three experiments were performed using fish ranging from 145 g to 3 kg and testing different diets, replacing FO up to 100%. Zootechnical performance was similar among treatments in all experiments. Changing the lipid source in the diet resulted in EPA and DHA digestibility of greater than 96%. Sensory characteristics of raw fish fillets were similar among treatments, supporting a similar sensorial experience with the replacement of FO with no impact on consumers. Overall, results confirm that the AO tested here enables the sustainable growth of Atlantic salmon aquaculture by helping to maintain a level of EPA and DHA in the fish fillets, without detriment to zootechnical performance and sensory characteristics, while simultaneously contributing to a reduced marine footprint for aquafeeds.